Reconstructing the Provisions on the Abatement of Pretrial Proceedings in Indonesian Criminal Procedure Law: Ensuring Equality Before the Law - Negara, Dharma Setiawan; Susilo, Erwin; Lufsiana, Lufsiana (CV. Social Politic Genius (SIGn), 2023)
Pretrial proceedings were designed as an instrument of judicial oversight to protect human rights from the arbitrariness of law enforcement authorities. Nevertheless, this philosophical expectation is contradicted by the reality of procedural malfunctions arising from legal loopholes in application abatement provisions. This research aims to examine the respondent’s power over case transfers critically and to formulate a norm reconstruction design for time limitations. This type of research is normative legal research that integrates the statutory, conceptual, case, and comparative approaches. Syllogistic analysis juxtaposes the ideal norms of justice with empirical findings from case studies of various court decisions. The research results show that the absence of a binding time limit has led to hasty case transfers by state instruments to evade judicial scrutiny. By overcoming this state of emergency, this research offers a novel, definitive time-limit protection mechanism design. For detained suspects, the validity of a case transfer is limited to 21 days from the date of the application’s registration. Conversely, for undetained suspects, the abatement provision is eliminated, subject to the prerequisite of physical presence at the hearing. Ultimately, the separation of time limits based on detention status constitutes the highest realization of substantive equality, dismantling state domination over the individual. This research recommends that the Supreme Court revoke the relevant administrative guidelines and urges lawmakers to incorporate this differentiation scheme into the renewal of the national criminal procedure law.